Fairy tail. 49 - Mashima, Hiro, 1977- (Kodansha Comics, 2015)
"Fairy Tail's managed to stop the resurrection of End, the most powerful demon in the Book of Zeref, and with it comes victory over Tartaros! But the dragon of darkness Acnologia is still fighting the Fire Dragon King, Igneel, and to make matters worse, Zeref the Black Wizard himself appears before Natsu! With this crucial confrontation still playing out, Guild Master Makarov makes a critical decision! And with it, Natsu, Lucy, and everybody else take a first step into a brand new chapter of their adventure!"--provided from Amazon.com.